City futures and transport - Banister, D (Amsterdam institute for Metropolitan and International Development Studies, 2006)
Transport planning has a crisis of identity and its future is uncertain, particularly as the increasing complexity of cities and societies make simple approaches to analysis, which views transport congestion as the problem and transport as the solution. This paper turns the problem the other way round and looks at city futures, desirable and likely, to establish the role that transport should play in achieving these visions. It will challenge two of the fundamental tenets of transport analysis, namely the treatment of travel as a derived demand and the desire for faster and more travel, including the key concept of travel time reductions. The advent of Information and Communications Technologies (ICT) have allowed broadband access to new forms of communications and networking, and this again suggests that all patterns of activity within the city will change to adapt to the new opportunities presented. Four principles for a new approach to sustainable urban development and transport will be presented, based on reducing the need to travel, modal shift, distance reduction and efficiency increases. Key to such a shift in thinking is the creation of spaces and localities in the city that are attractive and affordable for people to live in – neighbourhood quality is central to sustainable urban development. This means that transport planning must involve the people so that there is an understanding of the rationale behind the policy changes and that behavioural change follows. Public acceptability is central to the successful implementation of radical change, and it must involve community and stakeholder commitment to the process of discussion, decision making and implementation. This would include novel methods for participation, the use of demonstration projects, better communication and advice, and consideration of the means by which individual values can be matched more effectively with broader social and community values. The final part of the paper presents some of the necessary policy changes, both technological and behavioural, that must be made if sustainable urban development is to taker place. It also comments on whether there are the necessary institutional structures present to move from the traditional sector based approach to a more appropriate multisector based approach to decision making and implementation, so that transport planning is more effectively embedded within urban planning and the longer term visions of sustainable cities.